Maternal CASPR2 antibodies and neurodevelopmental disorders in the offspring: epidemiological findings and an animal model. (23rd February 2017) - Coutinho, Ester; Menassa, David; Jacobson, Leslie; West, Steven; Domingos, Joana; Moloney, Teresa; Pedersen, Marianne G; Benros, Michael E; Lang, Bethan; Bennett, David; Harrison, Paul J; Mortensen, Preben B; et al.
Abstract: Background: CNS disorders can be caused by IgG antibodies to neuronal surface proteins, and these antibodies have the potential to cross the placenta. Since some of them target proteins involved in neurodevelopment, such as contactin-associated protein-2 (CASPR2), we hypothesised that they could alter developing neuronal circuits in utero and lead to neurodevelopmental disorders in the children. Methods: A dual approach to the study was undertaken. First, we studied pregnancy serum samples from two population-based Danish cohorts: a cohort of women with postpartum psychosis and a cohort of mothers of children with mental retardation and other disorders of psychological development (MR–DPD), each with individually matched controls. We screened them for the presence of antibodies to CASPR2. Then, we assessed the effects of in-utero exposure to the antibodies in a mouse maternal-to-fetal model. Findings: The combined results from these two cohorts showed that maternal antibodies to CASPR2 were associated with an increased risk of MR–DPD in the children: eight (4·4%) of 182 mothers of MR–DPD children had CASPR2 antibodies compared with only three (0·9%) of 347 mothers of children without this diagnosis (p=0·01). This association was explored by injection of mouse dams with IgG purified from CASPR2-antibody-positive patients, or from healthy controls. The mouse offspring had long-term behavioural sequelae, manifested as deficits in social interaction and social activities, and increased repetitive, non-social behaviours. When they were culled at 12 months, their brains showed abnormal migration of cortical projection neurons, increased microglial activation, and reduction in the number of glutamatergic synapses, confirming that there had been long-term changes in neurodevelopment. Interpretation: CASPR2 was identified as a specific target for maternal antibodies that can alter brain development in utero, resulting in long-term behavioural deficits and permanent abnormalities at the cellular and synaptic level. These results should encourage further epidemiological and experimental studies to confirm and explore further how CASPR2 and other maternal antibodies can lead to neurodevelopmental disorders in children. Funding: EC was funded by the Programme for Advanced Medical Education at the Calouste Gulbenkian Foundation. This work was also supported by the Stanley Medical Research Institute. Resources were provided by the Nuffield Department of Clinical Neurosciences.